Amaranth as a natural food colorant source: Survey of germplasm and optimization of extraction methods for betalain pigments - Howard, Jay E.; Villamil, Maria B.; Riggins, Chance W. (Frontiers in Plant Science, 2022)
Growing consumer demands for healthier foods have evoked trends in the food industry to replace synthetically produced colorants with naturally derived alternatives. Anthocyanins currently comprise the bulk of the natural colorant market, but betalains offer advantages where anthocyanins have limits. Amaranthus species are appealing betalain sources given their extensive pigmentation patterns and recognized food status around the world. An advantage of amaranths as natural food colorants is that, when grown as leafy vegetables, water extracts would be compliant with U.S. Food and Drug Administration guidelines as “vegetable juice” colorants. Thus, we developed a methodology based on U.S. FDA guidelines to investigate betalain diversity among forty-eight amaranth accessions grown as leafy vegetables. Total betacyanin concentrations ranged from 4.7 to 478.8mg/100g dry weight, with amaranthin and isoamaranthin identified as major constituents. Our findings will guide future research on amaranths to determine economic viability and suitability for growing natural colorant markets.